Parents' Attitudes towards Inclusive Education - Amka Amka (Universitas Muhammadiyah Sidoarjo, 2019)
Inclusive education has become an international education policy. Many countries already have legislation for inclusive education based on international human rights treaties such as the 1994 Salamanca Statement and UNESCO Action Framework and the United Nations Convention on the Rights of Persons with Disabilities. Indonesia has become one of the countries that applies inclusive education in education laws and policies, and has required all provinces to implement inclusive education. The success of inclusive education requires the support of parents. This study highlights the attitudes of parents towards inclusive education. at the Keraton 4 Martapura Elementary School. The purpose of this study is to obtain an overview of the attitudes of parents of children with special needs for inclusive education services. A total of 40 parents of children with special needs were interviewed to get a picture of attitudes. The results of this study showed the attitudes of parents with special needs to accept the concept of inclusive.